MITOS MALE BEAUTY STANDRAD DALAM IKLAN MS GLOW MEN VERSI BABE CABITA DAN MARSHEL WIDIANTO DI INSTAGRAM - Sayekti, Eva Ken (The Commercium, 2022)
Abstract The concept of male beauty standard is a concept of the handsome standards that indonesians have entrusted men with. The concept of male beauty standard was never far from a physical trait deemed worthy of esteem or admiration. In this study, the writer's concept of male beauty standard is reflected in the Ms. Glow men version of babe cabita and marshel widianto AD on instagram. Where the AD did claim to have created a new male beauty standard concept that did not judge men by any physical description. The purpose of this study is to find out how the myth of the male beauty standard concept in the skincare glow version of babe cabita and marshel widianto AD is. That way the author knows the truth of our claims made by Ms. Glow for men through those ads. The study involves a qualitative approach and data collected using Roland barthes' semiotics method. There are three aspects of emphasis: dennotation, connotation and myth to analyze elements that were never seen in the skincare glow version of Babe Cabita and Marshel Widianto. Research shows that the Ms. Glow men version of Babe Cabita and Marshel Widianto AD in instagram just overshadow the meaning of the male beauty standard concept that if it can't meet one standard there is another standard. Because there is still a hegemonic element in the AD by promoting the benefits of Ms. Glow men that can whiten the skin. Keywords: Male Beauty Standard, MS.Glow Men Version Babe Cabita and Marshel Widianto AD, Roland Barthes Semiotics, Hegemonic.